Using lowpass and highpass filters to form UWB bandpass filter - Devkumar S.; Chakrabarty C.K. (2023)
In this paper, a new UWB Bandpass filter is proposed. The combination of an open-circuited lowpass filter with a short-circuited highpass filter is used to dsign a UWB BPF. This papper also explains the new approach in designing a UWB BPF. The performanece of this design in terms of its reflection loss, isertion loss and group delay was also compared with the previously designed UWB BPF's Simu1ations were carried out using the CST Microwave Studio software to demonstrate the reflection loss (S11) insertion loss (S21) and group delay of this design. 2008 IEEE.